Product and Service Marketing Workshop by Using Online Marketplace in Durin Tonggal Village (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Durin Tonggal is one of the villages in Pancur Batu sub-district, Deli Serdang Regency, North Sumatra province, Indonesia. 60% of the people in Durin Tonggal Village work as entrepreneurs, especially small business entrepreneurs such as souvenir businesses, snack & catering businesses, and so on. The activities of Pengabdian Kepada Masyarakat that have been carried out have focused on increasing understanding of the use of online media as a promotional tool for small business entrepreneurs in the Village of Durin Tonggal. With increasing public understanding, it can expand the buyers of products so that it will increase the sales of products and services. Increased sales transactions will result in high economic turnover so that this PKM activity is expected to improve the lives of Durin Tonggal villagers.